2013
DOI: 10.1007/s11908-013-0373-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae: Laboratory Detection and Infection Control Practices

Abstract: Over the past decade, carbapenem-resistant Enterobacteriaceae (CRE) have become one of the most challenging problems in infectious diseases. Fast and accurate detection of carbapenem resistance is crucial for guiding the treatment of the individual patient as well as for instituting proper infection control measures to limit the spread of the organism. Currently there are no consensus recommendations for screening, detection and confirmation of CRE either on the clinical or the laboratory side. In infection co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Although Israeli and U.S. guidelines consider a patient's region or country of origin in assessing risk, the European Centre for Disease Prevention and Control rejects classifying countries as low‐ or high‐risk and screening only patients from the latter group, as the true CRE prevalence of any country is unknown . Ideally, patients screened on admission should be placed on preemptive contact precautions in a single room until the test results are reported …”
Section: Interventions To Prevent Transmission Of Crementioning
confidence: 99%
See 1 more Smart Citation
“…Although Israeli and U.S. guidelines consider a patient's region or country of origin in assessing risk, the European Centre for Disease Prevention and Control rejects classifying countries as low‐ or high‐risk and screening only patients from the latter group, as the true CRE prevalence of any country is unknown . Ideally, patients screened on admission should be placed on preemptive contact precautions in a single room until the test results are reported …”
Section: Interventions To Prevent Transmission Of Crementioning
confidence: 99%
“…149 Ideally, patients screened on admission should be placed on preemptive contact precautions in a single room until the test results are reported. 150 Screening during the course of hospitalization is recommended for patients who are epidemiologically linked to a patient with newly detected CRE carriage or infection. If the index case is detected in a high-risk unit, such as an intensive care or transplant unit, all other patients in the unit should undergo screening.…”
Section: Active Surveillancementioning
confidence: 99%
“…Given the multi-faceted nature of infection prevention bundles, the individual contribution of each intervention has not clearly been established, but the authors conclude that traditional targeted interventions (such as contact isolation), and systems approaches (including hand hygiene compliance and feedback) are essential to CRE mitigation. The role of these infection control practices and their inclusion in several national guidelines is largely based on outbreak experience rather than clinical trial data and was recently reviewed by Kruse and colleagues [35]. Clinicians involved in the NIH Clinical Center CRE outbreak echoed the need for diligent compliance with hand hygiene and other infection prevention protocols in a recent editorial on the future of CRE management [36].…”
Section: Infection Control and Public Healthmentioning
confidence: 99%
“…The combination of doripenem and ertapenem was more active than either drug alone in both an in vitro chemostat model and a murine thigh infection model [35]. …”
Section: Emerging Therapiesmentioning
confidence: 99%
“…This resistance gene has been reported in most species of Enterobacteriaceae, but it is most commonly found in Klebsiella pneumoniae. Timely detection of carbapenem resistance is critical for prompt optimization of antimicrobial therapy, but the sensitivity of antimicrobial susceptibility testing methods for CRE detection is variable and turnaround time can be slow (6)(7)(8)(9)(10). It has been demonstrated that in vitro detection of K. pneumoniae carbapenemase (KPC) expression can be difficult, varying by bacterial species and level of enzyme expression.…”
mentioning
confidence: 99%